Giardia duodenalis genotyping not linked to clinical symptomatology and nutritional status of school-aged children of Soledad and Galapa municipality schools, Atlántico, Colombia (2022)
Giardia duodenalis genotypes A and B have been reported in Colombia. The population consisted of 235 schoolchildren whose ages ranged from 2 to 10 yr of age from the municipalities of Soledad and Galapa in the department of Atlántico, Colombia. Fecal samples were obtained and then analyzed in triplicate using the sedimentation in formalin-ether (Ritchie's method) and direct examination techniques. Of the 235 fecal samples, 35 samples were positive for G. duodenalis; positive samples were concentrated in a sucrose gradient and sonicated for 3 cycles of 20 sec. DNA extraction was performed, and the parasites were genotyped by conventional PCR amplifying a region of the β-giardin gene. A general prevalence of G. duodenalis of 13.2% was found, and of these genotyped samples, 13 (56.7%) and 7 (20%) corresponded to genotype A, 1 (4.3%), and 3 (25%) corresponded to genotype B, and 9 (39.1%) and 2 (16.7%) were not defined, in the municipalities Soledad and Galapa, respectively. Additionally, 23 children were diagnosed with symptomatologic giardiasis, and 12 were asymptomatic; the most relevant symptoms were abdominal pain (7, 20%) and diarrhea (13, 56.7%). The nutritional status of children with Giardia genotypes A and B were as follows: 3 in a state of malnutrition (10%), 10 normal (33.3%), and 6 overweight and obese (20%) with genotype A, and 1 in a state of malnutrition (3.3%) and 3 normal (10%) with genotype B. The genotypes found in G. duodenalis did not show an association with nutritional status or with the clinical manifestations evaluated in schoolchildren.